Global gifts : the material culture of diplomacy in early modern Eurasia - Biedermann, Zoltán; Gerritson, Anne, 1967-; Riello, Giorgio (Studies in comparative world history., 2018)
This anthology explores the role that art and material goods played in diplomatic relations and political exchanges between Asia, Africa, and Europe in the early modern world. The authors challenge the idea that there was a European primacy in the practice of gift giving through a wide panoramic review of imperial encounters between Europeans (including the Portuguese, French, Dutch, and English) and Asian empires (including Ottoman, Persian, Mughal, Sri Lankan, Chinese, and Japanese cases). They examine how those exchanges influenced the global production and circulation of art and material culture, and explore the types of gifts exchanged, the chosen materials, and the manner of their presentation. Global Gifts establishes new parameters for the study of the material and aesthetic culture of Eurasian relations before 1800, exploring the meaning of artistic objects in global diplomacy and the existence of economic and aesthetic values mutually intelligible across cultural boundaries.